Requirements Engineering and Management - A development of a Requirements Management Metrics Portal - Hou, Kebing; Jonsson, Alexander M. (My University, 2009)
This thesis report describes the benefits of employing metrics within Volvo Requirements Management and Project Management. It further describes the effectiveness of implementing these metrics in an automated project measuring system such as the prototype developed. Disciplines such a Systems Engineering, Requirements Engineering and Requirements Management were extensively studied in order to have enough knowledge to propose useful metrics. A generic workflow for Volvo Complete Offer and Embedded Software departments was also proposed which could serve as the basis for creating new metrics that meet the organisation's goals. The prototype developed, Requirements Management Metrics Portal, gathers data (i.e. requirements) from the databases provided by Volvo, calculates the metrics using predefined base-measures and visualizes the results in charts as the chosen graphical presentation format.
Keywords: Datorteknik; Computer Engineering